Assessment of intellectual capital in joint-stock companies - Tamosiuniene, Rima; Survilaitė, Simona (Business: Theory and Practice, 2015)
The evaluation of intellectual capital factors is an essential part for the management of joint-stock companies. Many authors indicate that successful intellectual capital management increases value added in joint-stock companies. Nevertheless, intellectual capital is a complex and challenging concept as there is still no clear guidance, what the intellectual capital features and its structural parts are. Theoretical research revealed that scientists accentuate various intellectual capital parts depending basically on the type of their research, on the level of the research (micro, mezzo, macro), variables they selected to investigate and similar. This research paper gives an insight what drivers can be increasing value added in joint-stock companies.